Sistem Pakar Mendiagnosa Kerusakan Pada Mesin Penggilingan Padi Menggunakan Metode Naive Bayes - Ayuningsih, Devi; Hasibuan, Nelly Astuti (JURIKOM (Jurnal Riset Komputer), 2018)
A rice milling machine is a machine that is used to facilitate the work of farmers to separate rice grains from their skin while maintaining the quality of rice and minimizing the loss of yield that often occurs in the process of rice formation which is done manually to get quality production. Expert systems can be used to help people solve problems that are usually resolved by experts. The difficulty of the community in finding an expert or understanding experts causes expert systems to be needed by one of them in the industrial field. The limited knowledge in identifying damage that often occurs in rice milling machines often makes it difficult for machine users to repair. This system is built to predict damage to rice milling machines using the application of the Naive Bayes method. This method is able to be the solution to the above problems because Naive Bayes are able to predict opportunities in the past. This system is created by taking data from one of the rice refineries consisting of damage data, and the symptoms which will then be entered into the naÃ¯ve Bayes formula, in order to find more accurate results.